Selective Laser Trabeculoplasty: A Clinical Review - Alon, Skaat (Journal of current glaucoma practice, 2013)
Selective laser trabeculoplasty (SLT) is a safe and effective treatment modality for lowering the intraocular pressure in patients with glaucoma. It achieves its results by selective absorption of energy in the trabecular pigmented cells, sparing adjacent cells and tissues from thermal damage, with minimal morphological tissue alteration following treatment. On the basis of the peer-reviewed medical literature, SLT is efficacious in lowering IOP, as initial treatment or when medical therapy is insufficient in all types of open-angle glaucoma in all races. SLT achieves intraocular pressure reduction similar to that of argon laser trabeculoplasty but without the tissue destruction and side effects. Observed side effects following SLT were almost uniformly transient and minor. We review highlights of recently published studies on the mechanisms and clinical outcome of SLT in order to address frequently raised issues pertinent to SLT in the clinical practice. Selective laser trabeculoplasty is a safe and effective treatment modality for lowering the intraocular pressure in patients with glaucoma. How to cite this article: Alon S. Selective Laser Trabeculoplasty: A Clinical Review. J Current Glau Prac 2013; 7(2):58-65.